Uremia-Associated Immunological Aging and Severity of COVID-19 Infection - Betjes, Michiel G. H. (Frontiers in Medicine, 2021)
One year after the start of the COVID-19 pandemic it has become clear that some groups of individuals are at particular high risk of a complicated course of infection resulting in high morbidity and mortality. Two specific risk factors are most prominent, old age and the presence of co-morbidity. Recent studies have shown that patients with compromised renal function, especially those treated with renal replacement therapy or having received a kidney transplant are at a much higher risk for severe COVID infection and increased mortality. This may be in part due to the increased prevalence of co-morbid conditions in these patients but specific alterations in their immune system, reflecting premature immunological ageing, may be equally important. In this review the different aspects, in particular thymus function and memory T cell expansion, of uremia-associated immunological ageing are reviewed with respect to COVID 19 infection. In essence, the decreased generation of naïve T cells may be instrumental in suboptimal anti-viral immune responses while the relatively uncontrolled expansion of effector T cells may facilitate the feared phase of the COVID-19 infection with excessive and live-threatening inflammation of the lung parenchyma.